The Effect Of Revenue And Income Tax Expense On Net Profit - Riftiasari, Dinar (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to determine and analyze the influence of revenue and income tax expense on net profit at PT. Midi Utama Indonesia Tbk which operates in the retail business in Indonesia, both partially and simultaneously. The population in this research is the quarterly financial reports of PT. Midi Utama Indonesia Tbk 2014-2023. The research sample includes data regarding revenue, income tax expense and net profit. The data analysis technique for this research uses the SPSS version 27 program. Based on the research results, it can be concluded that revenue partially influences net profit with a significance value of 0.000 0.05, Income Tax Expense partially influences net profit with a significance value of 0.000 0, 05, revenue and income tax expenses simultaneously influence net profit with a significance value of 0.000 0.05.